Hungarian Monitoring, 18 November 1990 . [Magyar rádiófigyelő], 1990. november 18 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Crisis sitting of Soviet parliament - Changes inside Albania - Peacekeepers in the Balkans - Bush in Prague - Domestic crisis in Bulgaria - Gorbachev in Rome Domestic Affairs: - Government delegation in Paris at the Helsinki Process talks - Árpád Göncz's experiences in the Far East - Five-party agreement on draft land law - Problems relating to Soviet troop withdrawals Economy: - Mercedes willing to cooperate with Ikarusz Külpolitika: - Válságülés a szovjet parlamentben - Belső változások Albániában - Békefenntartók a Balkánon - Bush Prágában - Belpolitikai válság Bulgáriában - Gorbacsov Rómában Belpolitika: - Kormányküldöttség Párizsban a helsinki folyamat ülésén - Göncz Árpád távol-keleti tapasztalatai - Ötpárti megegyezés a földtörvény tervezetéről - A szovjet csapatkivonással kapcsolatos problémák Gazdaság: - A Mercedes hajlandó kooperálni az Ikarus-szal